Using social media pedagogies to teach school mathematics in a selected Zimbabwean school during the COVID-19 pandemic - Mutambara, Lillias Hamufari Natsai; Tsakeni, Maria (Noyam Journals, 2022)
The COVID-19 pandemic tested teachers' and learners’ resilience to continue teaching and learning with the limited use of traditional classrooms. What became apparent was the need to find alternative ways to maintain the interactions between the teachers and the learners. This study explored the teaching and learning of secondary mathematics during the COVID-19 pandemic based on the community of inquiry framework. An explorative single case study design with forty learners and seven teachers from a rural school in Zimbabwe as participants was used. The purposive selection of the participants was based on their experiences of emergency remote learning and classes where COVID-19 protocols were observed. Data were collected through open-ended and closed questionnaires given to learners and structured and semi-structured interviews conducted with teachers. The qualitative data were analysed through thematic content analysis techniques. The findings show that in the wake of limited access to sufficient educational technologies and internet connectivity, teachers had to find alternative ways to teach mathematical problems by using already worked-out examples and voice notes, thereby reducing the teaching presence and teacher-learner interactions. However, the reduction of the teaching presence was compensated by increased self-regulated learning as learners tried to make sense of the examples shared through social media tools. The study recommends building teachers’ technological and pedagogical knowledge to teach mathematics using cheap social media applications to improve the teaching, social and cognitive presence.
Keywords: COVID-19 pandemic; Educational technologies; School mathematics; Social media pedagogies